FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP AUDIT REPORT LAG (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2013-2016) - Siti Laela Rahayu; Herry Laksito (Diponegoro Journal of Accounting, 2020)
The purpose of this research is to examine the impact of corporate size, audit firm status, audit complexity, directors board size, audit committee, ownership dispersion, and ownership concentration toward audit report lag in manufacturing company sector that listed on Indonesia Stock Exchange. The population in this study consists of service companies that listed on Indonesia Stock Exchange for 2013 till 2016.Sampling method that used is purposive sampling. The samples consist of 288 financial statements from 72 manufacture companies. Data used in this research is audited financial statements from each company that have been published. Multiple linear regression is used to be an analysis technique by SPSS version 23. The results of the analysis indicate that the variable company size, board size, and concentration of share ownership affect the audit report lag, which results are in accordance with the expected predictions. While variable KAP reputations, audit complexity, audit committee size, and the ownership dispersion do not affect the audit report lag, which results do not match the expected predictions.